Business Performance of Processed Amplang during the Covid-19 Pandemic in Sanga-Sanga District - Haqiqiansyah, Gusti; Purnamasari, Elly; Sugiharto, Eko (Fakultas Perikanan dan Kelautan Universitas Riau, 2023)
The Covid-19 pandemic has had quite a broad impact on the community's economic sector. This condition is also felt by Micro, Small and Medium Enterprises (MSME), including business actors in the fisheries and marine sectors. The study activities were carried out for 3 months from July to September 2021. This research used survey methods and interviews with business actors. The data collected is in the form of primary and secondary data. The data obtained were analyzed by descriptive qualitative. From the results of the study it can be seen that processing business actors are quite feeling the impact of this covid-19. The results of the study in terms of sales turnover experienced a significant decline (between 40 – 60%). The sluggish consumer demand for amplang products is due to various reasons such as restrictions on people's mobility (PPKM) and declining people's purchasing power.